Penguatan Daya Saing UMKM Tempe Daun Melalui Branding dan Tranformasi Digital - Nur Alfiyah, Putri; Putri Indriani, Agnesia; Dwi Elviyana, Anisya; Dian Rahmawati, Dinni; Awali Rahmadani, Regita (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
To improve the competitiveness of Micro, Small and Medium Enterprises (MSMEs), digital marketing is essential. One example is the Tempe Daun in Loh Sumber Village, Loa Kulu District, Kutai Kartanegara. This MSMEs still uses conventional marketing methods and cannot reach a wide market. This community service program aims to assist MSMEs with branding strategies and the use of digital technology to get more customers (Tiani et al., 2024). Preliminary studies are conducted to understand the business conditions, interviews with business owners are conducted to collect data, the data was analyzed to identify the main problems, and mentoring and socialization are used to build strategies. This activity was carried out in several steps, such as creating a Shopee seller account, registering and tracking the business locations on Google Maps, providing training on logo creation and branding design using Canva, and socializing with business owners to improve their understanding of digital marketing. The results of the activity showed that using branding and digital marketing strategies increased the visibility of Tempe Daun products, making them better known in Loh Sumber Village and in other areas. In addition, these efforts encourages business owners to use online platforms more frequently to increase their business sales. In conclusion, Tempe Daun MSMEs have successfully utilized digital technology through this service program. This discovery is important because it is an example of a simple yet effective innovation that can be applied by other MSMEs to improve their competitiveness and business sustainability.